Structural Relationships of Factors Which Impact on Learner Achievement in Online Learning Environment - Im, Tami; Kang, Minseok (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
The purpose of this study is to identify relationships of learners’ achievement goal orientation, self-regulation, test-anxiety, self-efficacy, participation, satisfaction, and achievement in online learning environments in Korea. A total of 1,832 student responses from a Korean cyber university were used to find structural relationships of factors. Causal relationships among various variables are provided as results of this study. Achievement goal orientation –approach, self-regulated learning, test-anxiety, and self-efficacy, were positively related to participation; however, achievement goal orientation-avoidance was negatively related to participation. Test-anxiety was directly related to learning achievement and it was found that participation affected learning satisfaction and learning achievement. It was also revealed that learning satisfaction was related to learning achievement. Results of this study suggest that a comprehensive management of learners’ psychological variables, such as achievement goal orientation, self-regulation, test-anxiety, self-efficacy for designing, and managing online learning environments is important to online learning organizations, instructors, and administrators for better learner support.